Existence and Uniqueness of Common Fixed Point on Complex Partial b-Metric Space - Arul Joseph Gnanaprakasam; Gunaseelan Mani; M. Aphane; Yaé U. Gaba (Journal of Function Spaces)
The fourth author Y. U. Gaba would like to dedicate this publication to his wife, Clémence A. Epse G., in celebration of her 33rd birthday